Compact hard X‐ray split‐and‐delay line for studying ultrafast dynamics at free‐electron laser sources. (11th June 2019) - Rysov, Rustam; Roseker, Wojciech; Walther, Michael; Grübel, Gerhard
Abstract : Presented here is a compact hard X‐ray split‐and‐delay line for studying ultrafast dynamics at free‐electron laser sources. The device is capable of splitting a single X‐ray pulse into two fractions with delay times from −5 to 815 ps and femtosecond resolution, operating continuously in a wide energy range between 7 and 16 keV. Abstract : A compact hard X‐ray split‐and‐delay line for studying ultrafast dynamics at free‐electron laser sources is presented. The device is capable of splitting a single X‐ray pulse into two fractions to introduce time delays from −5 to 815 ps with femtosecond resolution. The split‐and‐delay line can operate in a wide and continuous energy range between 7 and 16 keV. Compact dimensions of 60 × 60 × 30 cm with a total weight of about 60 kg make it portable and suitable for direct installation in an experimental hutch. The concept of the device is based on crystal diffraction. The piezo‐driven stages utilized in the device give nanometre positioning accuracy. On‐line monitoring systems based on X‐ray cameras and intensity monitors are implemented to provide active alignment feedback. Performance estimates of the system are also presented.